Hematological profile of water buffaloes: age and sex-related variations - Jaramillo, Ingrid; Agudelo-Florez, Piedad; Tobón, Julio César; Didier Ruiz, Jhon (Brazilian Journal of Veterinary Pathology, 2024)
The aim of this study was to establish blood reference intervals (RIs) and describe the effects of age and sex. In this cross-sectional study, we analyzed 1225 water buffaloes with nonvisible clinical signs of disease stratified by age and sex. The confidence intervals were calculated for each reference limit (95%, p<0.05). The data were analyzed in three age groups (calves, young, and adults) and two sex groups (females and males). The differences between age group, sex, and all the parameters were compared, and differences between age group, sex, and hematological parameters were found (p<0.05). Males showed higher values for red blood cell account, white blood cell account, and thrombocyte count; females showed higher values for Mean corpuscular volume and neutrophil parameters. Calves showed more hemoconcentration than in the other age groups. Young animals showed less total protein, neutrophils, and thrombocytes and a higher Mean corpuscular volume and lymphocyte count; statistically significant relation were found (p<0.05) in decreasing red blood cells, hemoglobin, packed cell volume, platelet, and total proteins, and increases in eosinophils and lymphocytes. The current study provides RIs and demonstrates changes associated with age and sex.